Boundary-value problems for the helmholtz equation in an angular domain. II - Podlipenko, Yu. K. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We investigate boundary-value problems that appear in the study of the diffraction of acoustic waves on an infinite cylinder (with a cross section of an arbitrary shape) placed inside a wedge so that the axis of the cylinder is parallel to the edge of the wedge. The potential theory which enables one to reduce these boundary-value problems to integral equations is elaborated.